Lis pendens and measures of inquiry: some reflections on the ECJ judgment of 4 may 2017 - Rodríguez Vázquez, María Ángeles (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
In its Judgment of 4 may 2017, in case C-29/16, Hanse Yachts AG c. Port D’Hiver Yachting SARL, Société Maritime Côte D’Azur y Compagnie Generali IARD SA, the ECJ establishes that a document instituting proceedings for the taking of evidence cannot be regarded, for the purposes of assessing a situation of lis pendens and of determining which court is the court first seised within the meaning of articles 27 and 30 of Regulation (EC) nº 44/2001, as also being the document instituting the substantive proceedings.